Medicare Expenditures and Health Care Utilization in a Multiethnic Community-based Population With Dementia From Incidence to Death. (October 2018) - Ornstein, Katherine A.; Zhu, Carolyn W.; Bollens-Lund, Evan; Aldridge, Melissa D.; Andrews, Howard; Schupf, Nicole; Stern, Yaakov
Abstract : Introduction: While individuals live with dementia for many years, utilization and expenditures from disease onset through the end-of-life period have not been examined in ethnically diverse samples. Methods: We used a multiethnic, population-based, prospective study of cognitive aging (Washington Heights-Inwood Columbia Aging Project) linked to Medicare claims to examine total Medicare expenditures and health care utilization among individuals with clinically diagnosed incident dementia from disease onset to death. Results: High-intensity treatment (hospitalizations, life-sustaining procedures) was common and mean Medicare expenditures per year after diagnosis was $69, 000. Non-Hispanic blacks exhibited higher spending relative to Hispanics and non-Hispanic whites 1 year after diagnosis. Non-Hispanic blacks had higher total (mean=$205, 000) Medicare expenditures from diagnosis to death compared with non-Hispanic whites (mean=$118, 000). Hispanics' total expenditures and utilization after diagnosis was similar to non-Hispanic whites despite living longer with dementia. Discussion: Health care spending for patients with dementia after diagnosis through the end-of-life is high and varies by ethnicity. Abstract : Supplemental Digital Content is available in the text.